Bacteriocyte plasticity in pea aphids facing amino acid stress or starvation during development - Ribeiro Lopes, Mélanie; Gaget, Karen; Renoz, François; Duport, Gabrielle; Balmand, Séverine; Charles, Hubert; Callaerts, Patrick; Calevro, Federica (Frontiers in Physiology, 2022)
An important contributing factor to the evolutionary success of insects is nutritional association with microbial symbionts, which provide the host insects with nutrients lacking in their unbalanced diets. These symbionts are often compartmentalized in specialized cells of the host, the bacteriocytes. Even though bacteriocytes were first described more than a century ago, few studies have explored their dynamics throughout the insect life cycle and in response to environmental stressors. Here, we use the Buchnera aphidicola/pea aphid symbiotic system to study how bacteriocytes are regulated in response to nutritional stress throughout aphid development. Using artificial diets, we analyzed the effects of depletion or excess of phenylalanine or leucine, two amino acids essential for aphid growth and whose biosynthetic pathways are shared between the host and the symbiont. Bacteriocytes responded dynamically to those treatments, while other tissues showed no obvious morphological change. Amino acid depletion resulted in an increase in bacteriocyte numbers, with the extent of the increase depending on the amino acid, while excess either caused a decrease (for leucine) or an increase (for phenylalanine). Only a limited impact on survival and fecundity was observed, suggesting that the adjustment in bacteriocyte (and symbiont) numbers is sufficient to withstand these nutritional challenges. We also studied the impact of more extreme conditions by exposing aphids to a 24 h starvation period at the beginning of nymphal development. This led to a dramatic drop in aphid survival and fecundity and a significant developmental delay. Again, bacteriocytes responded dynamically, with a considerable decrease in number and size, correlated with a decrease in the number of symbionts, which were prematurely degraded by the lysosomal system. This study shows how bacteriocyte dynamics is integrated in the physiology of insects and highlights the high plasticity of these cells.